Functional promiscuity in a mammalian chemosensory system: extensive expression of vomeronasal receptors in the main olfactory epithelium of mouse lemurs - Hohenbrink, Philipp; Dempewolf, Silke; Zimmermann, Elke; Mundy, Nicholas I.; Radespiel, Ute (Frontiers in Neuroanatomy, 2014)
The vomeronasal organ (VNO) is functional in most terrestrial mammals, though progressively reduced in the primate lineage, and is used for intraspecific communication and predator recognition. Vomeronasal receptor (VR) genes comprise two families of chemosensory genes (V1R and V2R) that have been considered to be specific for the VNO. However, recently a large number of VRs were reported to be expressed in the main olfactory epithelium (MOE) of mice, but there is little knowledge of the expression of these genes outside of rodents. To explore the function of VR genes in mammalian evolution, we analyzed and compared the expression of 64 V1R and 2 V2R genes in the VNO and the MOE of the gray mouse lemur (Microcebus murinus), the primate with the largest known VR repertoire. We furthermore compared expression patterns in adults of both sexes and seasons, and in an infant. A large proportion (83–97%) of the VR loci was expressed in the VNO of all individuals. The repertoire in the infant was as rich as in adults, indicating reliance on olfactory communication from early postnatal development onwards. In concordance with mice, we also detected extensive expression of VRs in the MOE, with proportions of expressed loci in individuals ranging from 29 to 45%. TRPC2, which encodes a channel protein crucial for signal transduction via VRs, was co-expressed in the MOE in all individuals indicating likely functionality of expressed VR genes in the MOE. In summary, the large VR repertoire in mouse lemurs seems to be highly functional. Given the differences in the neural pathways of MOE and VNO signals, which project to higher cortical brain centers or the limbic system, respectively, this raises the intriguing possibility that the evolution of MOE-expression of VRs enabled mouse lemurs to adaptively diversify the processing of VR-encoded olfactory information.